Advances in business, management and entrepreneurship : proceedings of the 3rd Global Conference on Business Management & Entrepreneurship (GC-BME 3), 8 August 2018, Bandung, Indonesia /: proceedings of the 3rd Global Conference on Business Management & Entrepreneurship (GC-BME 3), 8 August 2018, Bandung, Indonesia. (2019) - Unknown
No abstract available